Types of Absorptive Capacity as Antecedents of Innovation Capability: Mediating Effect of Knowledge Management - Anita Silvianita; Tri Indra Wijaksana (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The idea of absorptive capacity has become one of the most crucial ideas in the field of strategic management since it is frequently seen as a crucial component in developing innovative potential. Observations have been made regarding whether knowledge management must be present. As a result, the function of knowledge management as a mediating variable to the links between potential and realized absorptive capacity, and ultimately their effects on innovation capability, is discussed in this paper.Methodology: 180 Business Administration graduates with relevant employment experience served as our source for the data. We then observed their potential and discovered their capacity for invention, knowledge management, and absorption using SEM-PLS with SmartPLS software which was utilized as an aid in our analysis of the outcomes.Finding: Our results show that there is no significant association between either type of absorptive capacity or innovative capability. Innovative capability does not greatly lag behind absorptive capacity, whether potential or realized. However, when knowledge management is incorporated as a mediating element, realized absorptive capacity has a positive and significant indirect impact on innovative capability.Conclusion: Knowledge management has a strong mediating effect on realized absorptive capacity and has a positive as well as significant indirect impact on innovative capability